Σελίδα 1 από 1

IMC 2016/1/3

Δημοσιεύτηκε: Πέμ Ιούλ 28, 2016 10:31 am
από Demetres
Έστω θετικός ακέραιος n και έστω πραγματικοί a_1,\ldots,a_n και b_1,\ldots,b_n με a_i + b_i > 0 για 1 \leqslant i \leqslant n. Να αποδειχθεί ότι

\displaystyle{ \sum_{i=1}^n \frac{a_ib_i - b_i^2}{a_i+b_i} \leqslant \frac{\sum_{i=1}^n a_i \sum_{i=1}^n b_i - \left( \sum_{i=1}^n b_i\right)^2}{\sum_{i=1}^n (a_i+b_i)}}

Re: IMC 2016/1/3

Δημοσιεύτηκε: Πέμ Ιούλ 28, 2016 12:31 pm
από dement
Ισχύει \displaystyle \sum_{i=1}^n \frac{a_i b_i - b_i^2}{a_i + b_i} = \sum_{i=1}^n \left( b_i - \frac{2 b_i^2}{a_i + b_i} \right) \leq \sum_{i=1}^n b_i - \frac{2 \left( \sum_{i=1}^n b_i \right)^2}{\sum_{i=1}^n (a_i + b_i)} (από Cauchy-Schwarz) =

\displaystyle = \frac{(\sum_{i=1}^n a_i) (\sum_{i=1}^n b_i) - (\sum_{i=1}^n b_i)^2}{\sum_{i=1}^n (a_i + b_i)}